The role of international financial integration in monetary policy transmission - Jing Cynthia Wu; Yinxi Xie; Ji Zhang (Bank of Canada, 2024)
Motivated by empirical evidence, we propose an open-economy New Keynesian model with financial integration that allows financial intermediaries to hold foreign long-term bonds. We find financial integration features an amplification for a domestic monetary policy shock and a negative spillover for a foreign shock. These results hold for conventional and unconventional monetary policies. Among various aspects of financial integration, the bond duration plays a major role, and our results cannot be replicated by a standard model of perfect risk sharing between households. Finally, we observe an important interaction between financial integration and trade openness and demonstrate trade alone does not have an economically meaningful impact on monetary policy transmission.
Keywords: E44; E52; F36; F42; 330; Central bank research; International financial markets; Monetary policy transmission